KAJIAN YURIDIS: STATUS KOMISI PEMBERANTASAN KORUPSI DALAM SISTEM KETATANEGARAAN INDONESIA - I Dewa a Gde Budiarta; Putu Andhika Kusuma Yadnya; I Nyoman Suandika (Universitas Mahendradatta, 2022)
This study will discuss further about the status of the KPK in the Indonesian constitutional system not only in terms of the 1945 Constitution of the Republic of Indonesia, but also from sharing the opinions of legal experts in the field of state administration, in this case as an example of the Corruption Eradication Commission (KPK). will be analyzed is about its status. From this problem the author tries to raise the status of the Corruption Eradication Commission in an Indonesian constitutional system and how the position of the Corruption Eradication Commission in the constitutional system of the Republic of Indonesia. This research was studied using normative research. The status of the Corruption Eradication Commission (KPK) in the Indonesian constitutional system is as a State Institution within the scope of executive power but is independent. The KPK is a supporting institution that is separate or even independent, from the executive department, but is actually